2007
DOI: 10.1007/s11064-007-9387-9
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin Prevents Blood Brain Barrier Damage Induced by Focal Cerebral Ischemia in Mice

Abstract: Recombinant human erythropoietin (rhEPO), a neurovascular protective agent, therapeutically supports angiogenesis after stroke by enhancing endogenous up-regulation of vascular endothelial growth factor (VEGF). Increased VEGF expression has been characterized to negatively impact the integrity of the blood brain barrier (BBB), causing brain edema and secondary injury. The present study investigated the rhEPO-induced BBB protection after stroke and how it might be achieved by affecting VEGF pathway. rhEPO treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 35 publications
1
32
2
Order By: Relevance
“…5,6,27 These results reveal the effects of EPO on BBB under pathological conditions, in accordance with findings of this study. We further investigated the mechanisms involved in order to determine whether EPO elicited its protective effects by regulating the expression of AQP4.…”
Section: Erythropoietin Protects Bbb From Disruptionsupporting
confidence: 91%
“…5,6,27 These results reveal the effects of EPO on BBB under pathological conditions, in accordance with findings of this study. We further investigated the mechanisms involved in order to determine whether EPO elicited its protective effects by regulating the expression of AQP4.…”
Section: Erythropoietin Protects Bbb From Disruptionsupporting
confidence: 91%
“…Epo Protected Enterocyte Barrier Function and ZO-1 Localization from Inflammatory Cytokine-induced Damages-Human milk is protective against NEC, and Epo is a human milk factor that has been shown to protect cell-cell barrier in endothelial cells and the blood-brain barrier in animals (15,16). We hypothesized that Epo may similarly protect intestinal epithelial barrier function.…”
Section: Zo-1 Silencing Impaired Ter and Barrier Function Inmentioning
confidence: 99%
“…Erythropoietin (Epo) is a human milk factor (14). Although first described as a major regulator of erythropoiesis, Epo exhibits additional biological activities, including protection of endothelial cell-cell and blood-brain barriers (15,16). Functional Epo receptors are present on the luminal side of villi in fetal and neonatal human and rat intestines (17,18), suggesting physiological roles of Epo in the developing gut.…”
mentioning
confidence: 99%
“…Some authors have suggested that its local expression in the brain is unrelated to CM, 78 whereas others find it strongly associated with protection against neurologic sequelae in survivors of CM. 79 EPO is an anti-apoptotic hormone that protects endothelial cells, 80 thereby conserving BBB function in a stroke model 81 . Another and perhaps more important property of EPO in the context of CM is its stimulatory effect on nitric oxide secretion caused by endothelial nitric oxide synthase, 82 which improves perfusion under experimental conditions.…”
Section: Hypoxia and Cerebralmentioning
confidence: 99%